Migration of intra caesarean intrauterine device to sigmoid colon: a case report - Behura, Jharna; Kumar, Sanjiva (International Journal of Research in Medical Sciences, 2019)
Post-partum intrauterine contraceptive device inserted during caesarean section provides long acting reversible contraception to women soon after birth. It is now well accepted for its safety and efficacy. Uterine perforation, which is one of the most serious complication of PPIUCD has rarely been reported following intracaesarean insertion. The thick uterine wall and placement under direct vision helps prevent perforation. However, migration of IUCD to peritoneal cavity, causing perforation of several adjacent organs can occur due to improper closure of the uterine incision. Migration to sigmoid colon is an extremely rare complication. Authors present the case of a 29-year-old woman who had a Cu T 380 A insertion during Caesarean section. After 12 months of insertion, the patient suffered abdominal pain gradually increasing in intensity and frequent episodes of bleeding per rectum. Laparoscopic exploration revealed IUCD perforating the sigmoid colon completely and adhesions of bowel loops to the sigmoid colon. Extraction using laparoscopic method by gently pulling the threads was unsuccessful and the patient was managed by laparotomy.